Desenvolvimentos previsíveis na Dogmática do Direito Penal e na Política Criminal = Absehbare Entwicklungen in Strafrechtsdogmatik und Kriminalpolitik - Hassemer, Winfried (Revista Eletrônica de Direito Penal e Política Criminal, 2013)
This article examines, in general, the influence of the Contemporary Criminal Policy on the future development of Criminal Law and Criminal Procedure Law, as well as the problems that may arise with regard to the flexibilization of the substantive and procedural criminal guarantees. Therefore are analyzed the indispensable elements of Criminal Law and Criminal Procedure Law in the State based on law. Finally, it is presented alternatives to the maintenance of criminal law and its guarantees and that, otherwise, can absorb the situations that should not be embraced by the Criminal Law.